USE OF HEMP BRAN IN THE PRODUCTION OF WHEAT BREAD - BLAZHENKO, MARIIA; FALENDYSH, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Human nutrition should be balanced, the body should receive the entire range of necessary substances from food consumption. For quite a long time and until today, one of the food products that is in almost every consumer's basket is bread and bakery products, and it is with these products that we can partially or completely ensure the supply of nutrients for the human body. Bread and bakery products are the most rational product to use in order to enrich their chemical composition to provide the majority of society. Hemp seed processing products are promising raw materials for expanding the range of bread and bakery products with increased nutritional and biological value due to their qualitative and quantitative chemical composition. Comparisons of the chemical composition of wheat flour of the first grade were made. It was established that the total content of proteins and fats in hemp seed processing products is higher than in wheat flour of the first grade. Hemp bran is a source of dietary fibers, their content is 11.2 times higher than in wheat flour of the first grade. The amino acid composition of protein and bran is balanced and the content of essential amino acids is higher compared to wheat flour of the first grade. Analysis of the fatty acid composition showed that the ratio of Omega-3 and Omega-6 fatty acids is closest to the ideal in hemp bran 1:3.9, while in hemp protein it is 1:3.4. A trial laboratory baking of bread from wheat flour of the first grade was carried out with the replacement of 15% by hemp protein and the additional introduction of hemp bran by 3, 5 and 7% to the mass of flour, respectively. A sample of wheat bread with a recipe without the addition of hemp bran and protein served as a control. The acidity of semi-finished products increased due to the introduction of hemp seed processing products, and the fermentation process of the dough also intensified. However, the structural-mechanical and visco-plastic properties of the experimental samples with the replacement of first-grade wheat flour by 15% with hemp protein and the additional addition of 3.5 and 7% of hemp bran have insignificantly lower results, which can be corrected with the help of technological process parameters.
Keywords: bread; bakery products; hemp bran; enrichment; chemical composition